Carcinoid tumor of the ovary: A mysterious puzzle - -, Thilagarani; Ajith Prasad, Sowmya Devi (Indian Journal of Case Reports, 2024)
Carcinoid tumor of the ovary is a rare neoplasm that may present as a solid mass or combined with mucinous tumors or teratomas. Primary ovarian carcinoid represents